2017
DOI: 10.14740/jnr455w
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Neuroinflammatory, Therapeutic and Neuroprotective Role of Alpha-Mangostin

Abstract: Alpha-mangostin (α-MG), one of the key xanthone derivatives, displays a multiplicity of curative qualities like antiinfective, anti-malarial, anticarcinogenic, antidiabetic actions as well as antioxidant properties. Furthermore, it has proven to have neuroprotective, hepatoprotective, and cardioprotective features, of which the anticarcinogenic action is the most auspicious. Additionally, several in vitro and in vivo analyses confirm that α-MG partakes in the major stages of tumor growth: initiation, promotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…Studies have shown that brain tissue is specifically susceptible to oxidative injury. This could perhaps because of its extreme utilization of oxygen resulting in consequential production of excessive amounts of reactive oxygen species (ROS)1 during oxidative phosphorylation (16,33,111). Also, secretion of enzymes like monoamine oxidase and tyrosine hydroxylase in brain results in hydrogen peroxide (H 2 O 2 ) production.…”
Section: Resveratrol On Glutamate Uptake and Glutamine Synthetasementioning
confidence: 99%
“…Studies have shown that brain tissue is specifically susceptible to oxidative injury. This could perhaps because of its extreme utilization of oxygen resulting in consequential production of excessive amounts of reactive oxygen species (ROS)1 during oxidative phosphorylation (16,33,111). Also, secretion of enzymes like monoamine oxidase and tyrosine hydroxylase in brain results in hydrogen peroxide (H 2 O 2 ) production.…”
Section: Resveratrol On Glutamate Uptake and Glutamine Synthetasementioning
confidence: 99%